Collaboration strategy in the development and inheritance of Archipelago’s Arts - Yuliawan Kasmahidayat; Hasanuddin Hasanuddin (Goodwood Publishing, 2025)
Purpose: To increase the value of repertoire in interactions between humans, religion, and the state as an effort to inherit the arts and culture of the archipelago. Research Methodology: In addition to primary data sources from resource persons at the art study sites, secondary data sources from various articles, journals, and videos from YouTube are also used in the SWOT analysis process. Results: The strategy for the inheritance of the archipelago's arts is found in the art of Kuda Renggong, which creates a creative, reactive, formative attitude, and synergizes with the development of Indonesian culture 5.0. Conclusions: Education plays a role in preserving cultural values and fostering social unity. Adapting Society 5.0 in Indonesia requires attention to cultural diversity. Collaborative strategies involving education, conservation, and creative industries are key. The Kuda Renggong performance exemplifies cultural innovation in the digital era. Limitations: The studies and analysis results in this article can be used as the basis for other research studies that analyze the influence of technological progress on the development of the cultural arts of the archipelago. Contribution: As a basis for studies based on Anthropology, Cultural Studies, and Art Education which are able to analyze various studies in multi-disciplinary ways.